Ethics violations: A survey of investment analysts - Veit, E. Theodore (Journal of business ethics, 1996)
The authors analyze the responses to a mail survey of securities analysts who were asked about their ethical behavior and the ethical behavior of people with whom they work. The findings show the types of ethical violations that occur and the frequency with which they occur. The findings also show how respondents deal with observed violations of ethical behavior. All responses are analyzed to determine if differences exist between the responses of analysts having different characteristics (gender, age, years of employment, and education), and differences in employment circumstances (firm size, firm type, buy side/sell side, U.S./Canada).